Analisis Kinerja Pelayanan Publik Perusahaan Daerah Air Minum Tirta Cendana Kabupaten Timor Tengah Utara - Tri Anggraini; Dimas Agustian; Detson Ray Halomoan Sitorus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the public service performance of the TTU Regency Regional Drinking Water Company (Perumnda). This research uses qualitative research methods with observation and interview methods. From the research findings, it was found that environmental quality greatly influences the quality of service provided. Environmental quality conditions related to demographics hurt the continuity of water that can be distributed and give rise to various complaints from the public. However, on the other hand, Perumnda Drinking Water District TTU continues to promote efforts to improve the quality of service results by increasing the number of customers by improving the quality of interactions through acceleration, accuracy, and transparency. The conclusion is that the performance of the public services of the TTU Regency Regional Drinking Water Company is greatly influenced by the environmental quality of the North Central Timor Regency.. Keyword: Drinking Water Corporation, Performance Quality, Publik Service